Bioinspired palladium-doped manganese oxide nanocorns: a remarkable antimicrobial agent targeting phyto/animal pathogens - Sagar Vikal; Yogendra K. Gautam; Ashwani Kumar; Ajay Kumar; Jyoti Singh; Dharmendra Pratap; Beer Pal Singh; Neetu Singh (Scientific Reports, 2023)
Abstract Microbial pathogens are known for causing great environmental stress, owing to which emerging challenges like lack of eco-friendly remediation measures, development of drug-resistant and mutational microbial strains, etc., warrants novel and green routes as a stepping stone to serve such concerns sustainably. In the present study, palladium (Pd) doped manganese (II, III) oxide (Mn3O4) nanoparticles (NPs) were synthesized using an aqueous Syzygium aromaticum bud (ASAB) extract. Preliminary phytochemical analysis of ASAB extract indicates the presence of polyphenolics such as phenols, alkaloids, and flavonoids that can act as potential capping agents in NPs synthesis, which was later confirmed in FTIR analysis of pure and Pd-doped Mn3O4 NPs. XRD, Raman, and XPS analyses confirmed the Pd doping in Mn3O4 NPs. FESEM and HRTEM study reveals the mixed morphologies dominated by nanocorns appearance. Zeta potential investigation reveals high stability of the synthesized NPs in colloidal solutions. The developed Pd-doped Mn3O4 NPs were tested against two fungal phytopathogens, i.e., Sclerotinia sclerotiorum and Colletotrichum gloeosporioides, known for causing great economic losses in yield and quality of different plant species. The antifungal activity of synthesized Pd‐doped Mn3O4 NPs displayed a dose‐dependent response with a maximum of ~92%, and ~72% inhibition was recorded against S. sclerotiorum and C. gloeosporioides, respectively, at 1000 ppm concentration. However, C. gloeosporioides demonstrated higher sensitivity to Pd‐doped Mn3O4 NPs upto 500 ppm) treatment than S. sclerotiorum. The prepared NPs also showed significant antibacterial activity against Enterococcus faecalis. The Pd-doped Mn3O4 NPs were effective even at low treatment doses, i.e., 50–100 ppm, with the highest Zone of inhibition obtained at 1000 ppm concentration. Our findings provide a novel, eco-benign, and cost-effective approach for formulating a nanomaterial composition offering multifaceted utilities as an effective antimicrobial agent.